KINERJA PENGELOLA UMKM DILIHAT DARI LITERASI TEKNOLOGI DAN AKSES PERMODALAN - Fatkhurahman, Fatkhurahman; Novita, Novita (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
This study aims to analyze the influence of technological literacy and access to capital on the performance of Micro, Small, and Medium Enterprises (MSMEs) managers. The background of this study is based on the importance of MSMEs' abilities in facing the challenges of the digital era and limited access to financing sources which remain a major obstacle in business development. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires distributed to 90 MSME managers from various business sectors. The results of the study indicate that simultaneously, technological literacy and access to capital have a significant effect on MSME performance with a significance value of 0.000. Partially, both variables also have a positive and significant influence, where access to capital is the most dominant variable. The coefficient of determination (R²) value of 0.627 indicates that 62.7% of the variation in MSME manager performance can be explained by these two variables. This finding supports the Resource-Based View (RBV) theory which states that mastery of internal resources, such as digital capabilities and financial strength, is crucial for business success. This research recommends the need for policy interventions to promote technological literacy among MSMEs and increase access to affordable business financing. Strengthening these two aspects can sustainably improve the performance and competitiveness of MSMEs in the digital era.